Generic prescribing in India: a stumbling block - Kaur, Sukhpreet (International Journal of Research in Medical Sciences, 2020)
In India, there is 62% out-of-pocket health expenditure per capita and only 15% are covered by health insurance. The use of generics can save a lot of money which can be used for other health issues. But lack of knowledge about cost effectiveness of generic medicines among various health-care professionals had led to a low rate of generic medicine prescription in India. This review aims to identify the barriers in adoption of generic prescribing in clinical practice in India. A systematic literature review was conducted using various healthcare databases such as PubMed and google scholar. The literature search using various combination of keywords retrieved 2360 articles. After excluding duplicates, articles in languages other than English and based on relevance to subject only 15 articles were selected. The barriers to generic prescribing identified from reported literature can be broadly classified based on stakeholders of healthcare setting such as physicians, patients, pharmacist and government policies. The major barriers to generic prescribing identified were negative perception of various stakeholders, lack of awareness of regulatory standards, maturity of health care system, vulnerability of patients, lack of standard guidelines in brand substitution, incentives and influence of drug advertisements. In Indian set up, studies on impact evaluation of generic prescription, emphasizing the quality and cost saving by their use in clinical practice should be conducted. This evidence will help to build the confidence of various stakeholders towards implementing generic prescribing in clinical practice.